2021
DOI: 10.3390/digital1010002
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Practical Applications of Pedagogic Conversational Agents to Be Used in School and University Classrooms

Abstract: Pedagogic Conversational Agents (PCAs) can be defined as autonomous characters that cohabit learning environments with students to create rich learning interactions. Currently, there are many agents reported in the literature of this fast-evolving field. In this paper, several designs of PCAs used as instructors, students, or companions are reviewed using a taxonomy to analyze the possibilities that PCAs can bring into the classrooms. Finally, a discussion as to whether this technology could become the future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 43 publications
2
22
0
1
Order By: Relevance
“…Besides, the chatbots studied had a strong tendency to use English, at 89%. This high number aligns with results from (Pérez-Marín, 2021), where 75% of observed agents, as a related technology, were designed to interact in the English language. (Pérez-Marín, 2021) also shows that 42% of the analyzed chatbots had mixed interaction modalities.…”
Section: Related Worksupporting
confidence: 82%
See 4 more Smart Citations
“…Besides, the chatbots studied had a strong tendency to use English, at 89%. This high number aligns with results from (Pérez-Marín, 2021), where 75% of observed agents, as a related technology, were designed to interact in the English language. (Pérez-Marín, 2021) also shows that 42% of the analyzed chatbots had mixed interaction modalities.…”
Section: Related Worksupporting
confidence: 82%
“…This high number aligns with results from (Pérez-Marín, 2021), where 75% of observed agents, as a related technology, were designed to interact in the English language. (Pérez-Marín, 2021) also shows that 42% of the analyzed chatbots had mixed interaction modalities. Finally, (Hobert and Meyer von Wolff, 2019) observed that only 25% of examined chatbots were incorporated in formal learning settings, the majority of published material focuses on student-chatbot interaction only and does not enable student-student communication, as well as nearly two-thirds of the analyzed chatbots center only on a single domain.…”
Section: Related Worksupporting
confidence: 82%
See 3 more Smart Citations